The Idea of Haiti : Rethinking Crisis and Development - Polyne, Millery (Book collections on Project MUSE., 2013)
After Haiti was struck by a devastating earthquake on January 12, 2010, aid workers and offers of support poured in from around the world. Tellingly, though, news reports on the catastrophe and relief efforts frequently included a pejorative description of the country that outsiders were determined to rebuild: the troubled island nation, a nation plagued by political violence. There was much talk of inventing a "new" Haiti, which would presumably mimic Western modes of development and thus mitigate political instability and crisis. As contributors to this wide-ranging book reveal, Haiti has long been marginalized as an embodiment of alterity, as the other, and the idea of a new Haiti is actually nothing new. An investigation of the notion of newness through the lenses of history and literature, urban planning, religion, and governance, this book illuminates the politics and the narratives of Haiti's past and present. The essays, which grow from original research and in-depth interviews, examine how race, class, and national development inform the policies that envision re-creating the country.